Improving students' scientific literacy : Development of guided inquiry-based student worksheets on buffer solution material - Arif Sholahuddin; Normina Normina; Rilia Iriani (Jurnal Pendidikan Kimia, 2024)
Everyone must have scientific literacy to actively participate in advancing science, technology, and society. However, the scientific literacy skills of Indonesian students are still low. This research aims to develop student worksheets based on guided inquiry on buffer solution material to increase students' scientific literacy. This research applied 4D development research which includes the Definition, Design, Development, and Dissemination stages. At the definition stage, a needs analysis was carried out, while at the design stage, a draft of the student worksheet was made. At the development stage, the worksheet was validated by 5 validators. Furthermore, the revised worksheet was tested for readability by 10 students in class XI IPA. Finally, the revised worksheet was field tested on 32 students through a learning buffer solution in class with a guided inquiry strategy. This study employed a descriptive approach to assess the validity, practicality, and effectiveness of the worksheet. The findings indicate that the developed worksheet is highly valid, with an average validity score of 94.11% across the content, presentation, media, and language aspects, placing it in the very valid category. The worksheet also achieved a practicality score of 84%, indicating it is practical. Additionally, the worksheet improved students' scientific literacy with an N-gain value of 0.59. Therefore, it can be concluded that the worksheet can be used to improve students' scientific literacy through buffer solution learning.